2019
DOI: 10.3847/1538-4357/ab0e83
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gaia DR2 Parallaxes of Stars with VLBI Astrometry

Abstract: We compare the parallaxes of stars from VLBI astrometry in the literature to those in the Gaia DR2 catalog. Our full sample contains young stellar objects, evolved AGB stars, pulsars and other radio stars. Excluding AGB stars, which show significant discrepancies between Gaia and VLBI parallaxes, and stars in binary systems, we obtain an average, systematic, parallax offset of −75 ± 29 µas for Gaia DR2, consistent with their estimate of a parallax zero-point between −100 and 0 µas.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 70 publications
3
48
0
Order By: Relevance
“…IC1396A is a bright-rimmed globule complex, also known as "the Elephant Trunk Nebula," illuminated by HD206267, a Trapezium-like O star system (O6.5V + O9V), which is a part of the Cepheus OB2 association and is at a distance of 945 73 Collaboration 2018; Sicilia-Aguilar et al 2019). This value is consistent within the errors with the result from main-sequence fitting of the intermediate-mass (∼A-type) stars, 870±80 pc (Contreras et al 2002), particularly given a possible small bias in the Gaia results toward large distances (Xu et al 2019). IC1396A is at the western edge of the Tr37 cluster (Marschall & van Altena 1987;Platais et al 1998).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…IC1396A is a bright-rimmed globule complex, also known as "the Elephant Trunk Nebula," illuminated by HD206267, a Trapezium-like O star system (O6.5V + O9V), which is a part of the Cepheus OB2 association and is at a distance of 945 73 Collaboration 2018; Sicilia-Aguilar et al 2019). This value is consistent within the errors with the result from main-sequence fitting of the intermediate-mass (∼A-type) stars, 870±80 pc (Contreras et al 2002), particularly given a possible small bias in the Gaia results toward large distances (Xu et al 2019). IC1396A is at the western edge of the Tr37 cluster (Marschall & van Altena 1987;Platais et al 1998).…”
Section: Introductionsupporting
confidence: 81%
“…The nominal errors in the Gaia-estimated distance (Sicilia-Aguilar et al 2019) are too small to explain these shifts. However, there is evidence for a small bias toward underestimating parallaxes in Gaia (see summary in Xu et al 2019). A weighted average of all the measurements (Xu et al 2019) yields −53±3 μas, but this value is strongly influenced by the single input with the smallest quoted error.…”
Section: K-band Luminosity Function and Cmd Comparisonmentioning
confidence: 99%
“…Working with empirical eclipsing binary surface brightness-color relations, Graczyk et al (2019) estimated a zero-point offset of 31µas ± 11µas. Other results confirm this picture: using a statistical approach based on the effect of parallax errors on tangential velocities, Schönrich et al (2019) determined a zero-point offset of 54µas ± 6.0µas; applying a machine learning distance classifier using APOGEE spectroscopy, Leung & Bovy (2019) found a zero-point offset of 52.3µas ± 2.0µas; and Xu et al (2019) inferred an offset of 75µas ± 29µas with very long baseline interferometry astrometry. Most recently, Khan et al (2019) and Hall et al (2019) found offsets of 51.7µas ± 0.8µas (± ≈ 10µas when including spatially-correlated parallax errors) and 38.38 +13.54 −13.83 µas, by computing asteroseismic 1 The angle between the two fields of view of Gaia that allows an absolute measure of parallax.…”
Section: Introductionmentioning
confidence: 90%
“…reported a parallax offset of 0.082±0.033 mas using a sample of eclipsing binaries. In 2019, many more studies dealt with the Gaia parallax zero point and the value varies between 0.030 and 0.1 mas (0.031±0.11mas,Graczyk et al (2019); 0.054±0.006mas,Schönrich et al (2019); 0.0523±0.002 mas,Leung & Bovy (2019); 0.075±0.029mas,Xu et al (2019); 0.0517±0.0008mas,Khan et al (2019); 0.03838 +0.01354 −0.01383 mas,Hall et al (2019); and 0.0528±0.0024 mas,Zinn et al (2019)).…”
mentioning
confidence: 99%